The Value of Cytochemical Stains in the Diagnosis of Acute Leukemia - Deghady, Akram Abdel Moneim; Mansour, Amal Refaat; Elfahham, Bassma Alaa Alden Abd Elhamed (International Journal For Research In Health Sciences And Nursing, 2016)
Background: acute leukemia(AL) represents a clonal expansion and arrest at specific stage of normal myeloid or lymphoid hematopiosis that result in accumulation of malignant blast cells in the bone marrow and peripheral blood. Cytochemical stains play an important role in the diagnosis, classification and differentiation of acute leukemia. Aim: the aim of the present study is to evaluate the role of cytochemical stains in the diagnosis of acute leukemia compared to immunophenotyping by flowcytometry. Materials and Methods: Myeloperoxidase (MPO), Sudan Black B(SBB), Non Specific Esterase(NSE) and Periodic Acid Schiff (PAS) stains were done on thirty newly diagnosed acute leukemia patients admitted at the Alexandria University hospitals. Fifteen age matched healthy controls were included in the study. Results: The present study showed that Cytochemical stains (MPO, SBB, PAS and NSE), when coupled with morphology accurately diagnosed 93.3% of acute leukemia cases. A total of 13/15 (86.7%) ALL cases and 15/15 (100%) AML cases could be diagnosed correctly. MPO showed significant positive association with CD13 and CD33 and significant negative association with CD10, CD19 and CD2. SBB had significant positive association with CD13 and CD33 and negative association with CD 10 and CD19. NSE showed positive association with CD14 and negative association with CD13. PAS had only positive association with CD5. Conclusion: Cytochemical stains( namely MPO and SBB) are useful in the diagnosis of acute leukemia specially AML cases, their importance is particularly of value in developing countries as they are simple and do not need special equipments or highly trained persons.